BEYOND POSITIVISM IN ACCOUNTING: A LEGAL-PHILOSOPHICAL EXAMINATION OF ACCOUNTING AND AUDITING STANDARDS - ZM, Syehabudin (Scientium Law Review (SLR), 2024)
The achievement of accounting standards in a particular company or country, including information on the economy of a country and the development of a company, cannot be separated from the dominance of the positivist paradigm. However, it must be recognised that the occurrence of accounting fraud, which is basically based on the accounting standards in force, has left the question of how to overcome the lack of accounting standards, which has been occurring and recurring. This can be seen, among other things, in the financial crisis, which almost always occurs in a certain period of time, in corporate crime in various forms, and in the accounting and auditing standards that are created, which may not be neutral. Based on a philosophical-legal review, it is concluded that accounting is in the field of human or lived social sciences, which requires accountants and/or auditors to be open with stakeholders related to the field of mutual understanding or mutual understanding between subjects and subjects as fellow social beings. This beyond positivism shows that positivism in accounting/auditing is only for a certain cognitive interest (technical interest), which causes the elimination of various kinds of elements of subjectivity to find causal relationships that are undoubted. It is recommended that a responsive accounting/auditing model be developed between auditors and auditees and related stakeholders. The model is capable of reflecting competent accounting/auditing as a facilitator, responding to social needs and aspirations, and reaching out to competence through its forms of participation.